1974
DOI: 10.1113/expphysiol.1974.sp002280
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Fibres and Reticulin of Mammalian Muscle Spindles and Their Functional Significance

Abstract: The distribution of elastic fibres and reticulin of muscle spindles of man, cat and rat was studied by light and electron microscopy. The elastic fibres form a continuous network, arranged longitudinally around the intrafusal fibres; this is connected to a much finer elastic fibre network among the extrafusal muscle fibres. In general there are many more elastic fibres around nuclear bag fibres than around nuclear chain fibres and it seems unlikely that the 'elasticity' of nuclear chain fibres observed experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…No such additional contraction was observed, however, and the additional stretch was confined to the region of the sensory endings. It is concluded, therefore, that this additional stretch was the result of mechanical coupling between the intrafusal fibres at the spindle equator, due to connective tissue or elastic elements (Cooper & Gladden, 1974). Such coupling in the sensory region is not uncommon even though the nuclear bag and nuclear chain fibres slide easily past each other elsewhere in the spindle fluid space.…”
Section: Motor Control Of Isolated Spindlesmentioning
confidence: 98%
“…No such additional contraction was observed, however, and the additional stretch was confined to the region of the sensory endings. It is concluded, therefore, that this additional stretch was the result of mechanical coupling between the intrafusal fibres at the spindle equator, due to connective tissue or elastic elements (Cooper & Gladden, 1974). Such coupling in the sensory region is not uncommon even though the nuclear bag and nuclear chain fibres slide easily past each other elsewhere in the spindle fluid space.…”
Section: Motor Control Of Isolated Spindlesmentioning
confidence: 98%
“…In the case of the static nuclear bag fibre it seems likely that the extension of its primary sensory spiral is limited by the elastic and collagen tissue which braces the nuclear bag region (Cooper & Gladden, 1974). If so, then the extension of the spiral produced by the passive stretch will decrease progressively as the frequency of static y stimulation is increased.…”
Section: Glycogen Depletion In Intrafusal Fibresmentioning
confidence: 99%
“…Bessou and Pages [1975], also, observed that there was no mechanical interaction at all between individual nuclear bag fibres or between nuclear bag fibres and the bundle of nuclear chain fibres in the same spindle pole. There is always some mechanical linkage between the fibres in the equatorial region, however, which may be due either to connective tissue elements [Cooper and Gladden, 1974], or to the sensory terminations themselves. This mechanical coupling is most evident when one pole of a nuclear bag fibre or bundle of nuclear chain fibres pulls the entire primary sensory ending towards the active pole.…”
Section: Effect Of Intrafusal Activity On the Sensory Endingsmentioning
confidence: 99%